Archipelago of dreams: utopianism in Caribbean literature. Issue 1 (2nd January 2016) - Ashcroft, Bill
Abstract : The Caribbean is often considered to be the dysfunctional result of the twin catastrophes of colonialism and the sugar industry but it has become the most vibrant example of postcolonial transformation. Caribbean literature, owing to its radical creolisation of the English language has been at the forefront of the innovative production of Caribbean culture and a major factor in the region's capacity for future thinking. Rejecting nostalgia for an African or Asian past, this utopian dimension manifests itself in a vision of what Ernst Bloch calls Heimat – the home we have all sensed but never known. Focusing on Derek Walcott and Kamau Brathwaite, the essay examines the extent to which 'archipelagic thinking' enhances the utopian drive of the region's art and literature. The archipelago provides a model for a transformed world reality, a world of constant arrival and potentiality rather than origin and generates a form of dreaming that Bloch sees as the deepest function of art and literature.